2019
DOI: 10.1590/1984-70332019v19n4c63
|View full text |Cite
|
Sign up to set email alerts
|

CS58: new high yielding, salt and alkaline tolerant cultivar of Indian mustard

Abstract: CS58 is a newly developed, salt-tolerant, high-yielding Indian mustard variety from ICAR-CSSRI, Karnal, India, to harness the yield potential of saltaffected soils of India. It produced 24-25% higher seed yield than the national check varieties CS54 and Kranti and was well received and adopted by farmers in salt-affected areas of the country during on-farm demonstrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…These encouraging results are due to the application of balanced nutrients. These results are in line with the findings observed by Singh et al (2019) during the breeding of the mustard variety CS-58. The disease response of the strain KJ-238 was recorded with the check cultivar at the breeding station for two years (Table 8) and found that a sufficient amount of tolerance was present in the new strain for major diseases.…”
Section: -18 and 2018-19supporting
confidence: 92%
“…These encouraging results are due to the application of balanced nutrients. These results are in line with the findings observed by Singh et al (2019) during the breeding of the mustard variety CS-58. The disease response of the strain KJ-238 was recorded with the check cultivar at the breeding station for two years (Table 8) and found that a sufficient amount of tolerance was present in the new strain for major diseases.…”
Section: -18 and 2018-19supporting
confidence: 92%
“…A preliminary yield trial was conducted for two years for agronomic traits and resistance/tolerance to disease and mustard aphid infestation, along with the national check varieties. Replicated yield trials were conducted for three years under saline and alkaline conditions in salt-affected soils [30].…”
Section: Bulk Methodsmentioning
confidence: 99%
“…Salt tolerance was mainly controlled by dominant genes with an additive Breeding Mustard (Brassica juncea) for Salt Tolerance: Problems and Prospects DOI: http://dx.doi.org/10.5772/intechopen.94551 effect. The dominant effect played a major role and over-dominance might have existed in salt tolerance [29,30]. The traits like main shoot length, number of pods on main shoot and yield per plot could be improved effectively by selection as these might be controlled by additive genes.…”
Section: The Genetic Basis Of Salt Tolerance In Brassicaceaementioning
confidence: 99%
“…These reductions brought on by the adverse effects of salinity on plants, triggered by osmotic potential, preventing the root cells from obtaining the necessary water from the soil (Singh et al, 2019). As a result, some mineral nutrients that are dissolved in soil water cannot be taken up by plants.…”
Section: Effect Of Salinity On Growth Attributing Traits and Ionic Co...mentioning
confidence: 99%
“…Furthermore, decreased transpiration in salt-sensitive under increasing salinity compared to salt-tolerant genotypes may be caused by the toxicity of too much salt in the transpirational path, which damages cells in the transpiring leaves and inhibits growth (Table S4) (Singh & Sharma 2016). Salt-sensitive genotypes with increased ionic buildup have decreased leaf turgor, altered leaf shape, and reduced stomatal aperture, which in turn causes partial stomatal closure to limit water loss by transpiration and, as a result, lower stomatal conductance (Table S4) (Singh et al, 2019).…”
Section: Effect Of Salinity On Photosynthetic Traitsmentioning
confidence: 99%